2022
DOI: 10.1098/rstb.2021.0048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the neuropeptide–social cognition link in ageing: the mediating role of basic cognitive skills

Abstract: The roles of oxytocin (OT) and arginine-vasopressin (AVP) as crucial modulators of social cognition and related behaviours have been extensively addressed in the literature. The involvement of these neuropeptides in social cognition in ageing, however, and a potential mediating effect of basic cognitive capacities on this link, are not well understood. To fill these research gaps, this study assessed associations of plasma OT and AVP levels with dynamic emotion identification accuracy in generally healthy olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 161 publications
0
1
0
Order By: Relevance
“…Older women and men are a population understudied regarding the effect of OT on brain and behavioral function despite evidence that OT impacts functions that also change with age. For example, previous research has shown that OT modulates trust-related evaluations and decisions [7], dynamic social and emotional information processing [9,12], and functional brain networks relevant to decision-making, including the salience network and the default mode network [2,3]. Making these OT-related data publicly available is an important step toward enhancing scientific knowledge about the role of neuropeptides in shaping social cognition and social behavior in adulthood and aging [12].…”
Section: Data Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older women and men are a population understudied regarding the effect of OT on brain and behavioral function despite evidence that OT impacts functions that also change with age. For example, previous research has shown that OT modulates trust-related evaluations and decisions [7], dynamic social and emotional information processing [9,12], and functional brain networks relevant to decision-making, including the salience network and the default mode network [2,3]. Making these OT-related data publicly available is an important step toward enhancing scientific knowledge about the role of neuropeptides in shaping social cognition and social behavior in adulthood and aging [12].…”
Section: Data Descriptionmentioning
confidence: 99%
“…For example, previous research has shown that OT modulates trust-related evaluations and decisions [7], dynamic social and emotional information processing [9,12], and functional brain networks relevant to decision-making, including the salience network and the default mode network [2,3]. Making these OT-related data publicly available is an important step toward enhancing scientific knowledge about the role of neuropeptides in shaping social cognition and social behavior in adulthood and aging [12]. Additionally, OT research in Alzheimer's Disease and Related Dementias (ADRD) is very limited to date [13] and currently, it is unclear if intranasal OT administration attenuates cognitive impairments in aging and ADRD [14].…”
Section: Data Descriptionmentioning
confidence: 99%
“…They do not address the possible impact of a chronic enhancement of the oxytocinergic activity in the hypothalamus. In one study in elderly men, a negative association was actually found between plasma oxytocin and both crystallized and fluid cognitive skills (Polk et al, 1858). However, a systematic meta-analysis has been conducted on studies where central and peripheral oxytocin had been measured coordinately (Valstad et al, 2017).…”
Section: Oxytocin May Enhance Associative Learning and Modulate Perce...mentioning
confidence: 99%
“…However, the link with neuropeptides is understudied. Polk and colleagues [ 84 ] examine the link between oxytocin and social cognition in ageing, finding that higher levels of plasma oxytocin were associated with lower accuracy in emotion identification, while plasma levels of arginine-vasopressin had no relation to emotion identification accuracy. These novel findings support the involvement of oxytocin in age-related neural processes and the possible interactions between oxytocin and basic cognitive capacities.…”
Section: Oxytocin Interactions Beyond the Neuronmentioning
confidence: 99%